2018
DOI: 10.1186/s12935-017-0499-2
|View full text |Cite
|
Sign up to set email alerts
|

MiR-20a-5p suppresses tumor proliferation by targeting autophagy-related gene 7 in neuroblastoma

Abstract: BackgroundNeuroblastoma (NB) is the most common malignant tumor originating from the extracranial sympathetic nervous system in children. The molecular mechanisms underlying this disease are complex, and not completely understood.MethodsQuantitative real-time PCR (qRT-PCR) was applied to quantify the expression of miR-20a-5p and its target gene ATG7 in clinical NB tissues. The biological function of miR-20a-5p and ATG7 in SH-SY5Y cells was investigated through in vitro studies (Real-Time cell kinetic analyzer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
1
32
0
1
Order By: Relevance
“…We tested ten miR‐mimics of candidate TS miRNAs, namely miR‐34a, let‐7b, miR‐96, miR‐101, miR‐184, miR‐542, miR‐591, miR‐628, miR‐885, and miR‐20a, known to be underexpressed in NB, [ 18,26,38–43 ] along with negative controls by transfection of NB cell lines to evaluate cell viability. After pilot reverse transfection experiments with four different concentrations (50 × 10 ‐9 , 30 × 10 ‐9 , 3 × 10 ‐9 , and 0.3 × 10 ‐9 m ) of miR‐mimics, alamarBlue assay showed best results at a 50 × 10 ‐9 m and miR‐34a and let‐7b mimics resulted the most effective to induce a cell growth decrease at 7 d after transfection across the four NB cell lines ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…We tested ten miR‐mimics of candidate TS miRNAs, namely miR‐34a, let‐7b, miR‐96, miR‐101, miR‐184, miR‐542, miR‐591, miR‐628, miR‐885, and miR‐20a, known to be underexpressed in NB, [ 18,26,38–43 ] along with negative controls by transfection of NB cell lines to evaluate cell viability. After pilot reverse transfection experiments with four different concentrations (50 × 10 ‐9 , 30 × 10 ‐9 , 3 × 10 ‐9 , and 0.3 × 10 ‐9 m ) of miR‐mimics, alamarBlue assay showed best results at a 50 × 10 ‐9 m and miR‐34a and let‐7b mimics resulted the most effective to induce a cell growth decrease at 7 d after transfection across the four NB cell lines ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…These four miRNAs regulate tumorigenesis. [33][34][35][36] miR-106b-5p and miR-20a-5p also play important roles in central nervous system diseases. 30,37 Then, the levels of the four miRNAs were detected in PTZ-induced epilepsy rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have revealed the aberrant expression of miR-20a in various types of cancer, data on its function is inconsistent. For example, miR-20a overexpression inhibited the invasion of endometrial cancer cells [ 44 ] and the proliferation of neuroblastoma cells [ 45 ]. In contrast, miR-20a has been found to promote proliferation, invasion, and metastasis in hepatocellular carcinoma [ 46 ] and colorectal cancer cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%